The Complex Relation between Atrial Cardiomyopathy and Thrombogenesis - Elisa D’Alessandro; Joris Winters; Frans A. van Nieuwenhoven; Ulrich Schotten; Sander Verheule (Cells, 2022)
Heart disease, as well as systemic metabolic alterations, can leave a ‘fingerprint’ of structural and functional changes in the atrial myocardium, leading to the onset of atrial cardiomyopathy. As demonstrated in various animal models, some of these changes, such as fibrosis, cardiomyocyte hypertrophy and fatty infiltration, can increase vulnerability to atrial fibrillation (AF), the most relevant manifestation of atrial cardiomyopathy in clinical practice. Atrial cardiomyopathy accompanying AF is associated with thromboembolic events, such as stroke. The interaction between AF and stroke appears to be far more complicated than initially believed. AF and stroke share many risk factors whose underlying pathological processes can reinforce the development and progression of both cardiovascular conditions. In this review, we summarize the main mechanisms by which atrial cardiomyopathy, preceding AF, supports thrombogenic events within the atrial cavity and myocardial interstitial space. Moreover, we report the pleiotropic effects of activated coagulation factors on atrial remodeling, which may aggravate atrial cardiomyopathy. Finally, we address the complex association between AF and stroke, which can be explained by a multidirectional causal relation between atrial cardiomyopathy and hypercoagulability.